Ancient Greek view of perinatal risk issues: from myth to reality - Ariadne Malamitsi-Puchner; Despina D. Briana (Hygeia Press di Corridori Marinella, 2017)
Perinatology is a new medical discipline, originating in the 1960s, and aiming to prevent, diagnose and treat problems to the mother, fetus and neonate, prior, during and after delivery.  As above issues, applying to perinatology, are diachronically present, it is of interest to explore how they were previously viewed and coped with, particularly in ancient times. Ancient Greece is considered the cradle of Western medicine. Thus, the reasonable question arises, what did Ancient Greeks think about unusual conditions, encountered around delivery, like premature birth, small for gestational age babies, twin pregnancy, as well as inability to give birth vaginally, and thus to apply what we nowadays call an emergency cesarean section.